Influence of sorbitol on mechanical and physico-chemical properties of soy protein-based bioplastics processed by injection molding - Manuel Felix; Valme Carpintero; Alberto Romero; Antonio Guerrero (Polímeros)
Abstract Soy Protein Isolate (SPI) has been evaluated as useful candidate for the development of protein-based bioplastic materials processed by injection molding. The influence of sorbitol (SB) as plasticizer in mechanical properties and water uptake capacity was evaluated in SPI-based bioplastics. A mixing rheometer that allows monitoring torque and temperature during mixing and a small-scale-plunger-type injection molding machine were used to obtain SPI/Plasticizer blends and SPI-based bioplastics, respectively. Dynamic measurements were carried out to obtain mechanical spectra of different bioplastics. Moreover, the mechanical characterization was supplemented with uniaxial tensile tests. Additionally, the influence of SB in water uptake capacity was also evaluated. The introduction of SB leads to increase the rigidity of bioplastics as well as the water uptake capacity after 24h, however it involves a decrease in strain at break. Final bioplastics are plastic materials with both adequate properties for the substitution of conventional petroleum plastics and high biodegradability.